2021
DOI: 10.1016/j.nbd.2020.105141
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and neurobehavioral abnormalities in mice with a dominant-negative KCNB1 pathogenic variant

Abstract: Developmental and epileptic encephalopathies (DEE) are a group of severe epilepsies that usually present with intractable seizures, developmental delay, and often have elevated risk for premature mortality. Numerous genes have been identified as a monogenic cause of DEE, including KCNB1 . The voltage-gated potassium channel K v 2.1, encoded by KCNB1 , is primarily responsible for delayed rectifier potassium currents that are important regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 59 publications
6
36
0
Order By: Relevance
“…The naming of this cluster is based on a series of two papers written by Hakami [ 208 , 209 ] on antiseizure drugs, and may be related to ASD due to the higher prevalence of seizure and epilepsy diagnoses among these individuals [ 210 ]. Similarly, other contributing papers focused on understanding the genetic bases of epilepsy [ 211 , 212 , 213 ] and epilepsy treatment [ 214 , 215 ]. In this cluster, contributing papers frequently cited references from the International League Against Epilepsy (ILAE) in their clinical descriptions and classifications of different seizures and epilepsies (e.g., Scheffer et al [ 216 ], Fisher et al [ 217 , 218 ] with citation frequencies of 43, 12, and 8, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The naming of this cluster is based on a series of two papers written by Hakami [ 208 , 209 ] on antiseizure drugs, and may be related to ASD due to the higher prevalence of seizure and epilepsy diagnoses among these individuals [ 210 ]. Similarly, other contributing papers focused on understanding the genetic bases of epilepsy [ 211 , 212 , 213 ] and epilepsy treatment [ 214 , 215 ]. In this cluster, contributing papers frequently cited references from the International League Against Epilepsy (ILAE) in their clinical descriptions and classifications of different seizures and epilepsies (e.g., Scheffer et al [ 216 ], Fisher et al [ 217 , 218 ] with citation frequencies of 43, 12, and 8, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…DN effect is a classical molecular mechanism in genetic diseases, which is defined as the variant that will adversely affect the co-expressed wild-type activity. Many KCNB1 variants have disease effects in this way, such as the well-validated variant p.G379R, which interferes with wild-type functions in both potassium conductance and non-conductance aspects ( 7 , 15 ). We found that not all variants could be considered to have DN effects according to their functional results.…”
Section: Discussionmentioning
confidence: 99%
“…We found that not all variants could be considered to have DN effects according to their functional results. On the one hand, previous work has been mainly focused on unveiling their deficits in potassium conductance rather than their non-conductance roles ( 15 ). Here, we added an experiment on the KCNB1 protein expression in the heteromeric models, which aided us in identifying p.V408S as a DN effect variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…113 KCNB1 G379R mice recapitulate many features observed in individuals with developmental and epileptic encephalopathies (DEE) due to pathogenic variants in KCNB1 which encodes KV2.1. 114 Mutations of KCNB1 -(G379R, S347R, T374I) KV2.1 channel result in the early onset epileptic encephalopathy. 115 Voltage-gated potassium channel (KV2.1) functional defects caused by KCNB1 variants are associated with DEE.…”
Section: Potassium Channelsmentioning
confidence: 99%